Gradient metal nanoislands as a unified surface enhanced Raman scattering and surface enhanced infrared absorption platform for analytics. Issue 17 (31st July 2019) - Gkogkou, Dimitra; Shaykhutdinov, Timur; Kratz, Christoph; Oates, Thomas W. H.; Hildebrandt, Peter; Weidinger, Inez M.; Ly, Khoa Hoang; Esser, Norbert; Hinrichs, Karsten
Abstract : A metal nanoisland layer with varying plasmonic responses offers surface enhanced Raman scattering and infrared absorption optimal sites on a single surface. Abstract : In the last few decades, the use of plasmonics in vibrational spectroscopy has expanded the scope of (bio)analytical investigations. Nevertheless, there is a demand for a combined platform that can be simultaneously efficient for Surface Enhanced Raman Scattering (SERS) and Surface Enhanced Infrared Absorption (SEIRA). Here, we present a solution on the basis of a plasmonic Ag nanoparticle layer with a thickness gradient. The optical resonance along the layer varies from the visible to the infrared range offering optimal and intermediate sites for SERS and SEIRA of the analyte molecule (mercaptobenzonitrile). Enhancement factors for the same mode were determined to be ca. 10 4 and 170 for SERS and SEIRA, respectively. We present a full optical and vibrational characterization and demonstrate further tunability. The platform resolves reproducibility and comparability issues by a combination of the two methods. It also offers individualized solutions for different investigation conditions, i.e. a choice between excitation wavelengths and resonant Raman molecules. The multiple applicabilities of the presented unifying substrate can contribute to the expansion of the vibrational spectroscopic field and to analytics.